How I live now - Rosoff, Meg (New York Wendy Lamb Books, 2004)
To get away from her pregnant stepmother in New York City, fifteen-year-old Daisy goes to England to stay with her aunt and cousins, with whom she instantly bonds, but soon war breaks out and rips apart the family while devastating the land
1
Keywords: Cousins -- Fiction; Eating disorders -- Fiction; Family life -- England -- Fiction; Farm life -- England -- Fiction; War -- Fiction; England -- Fiction